2020
DOI: 10.1186/s12864-020-6640-y
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationship between Australian Fusarium oxysporum isolates and resolving the species complex using the multispecies coalescent model

Abstract: Background: The Fusarium oxysporum species complex (FOSC) is a ubiquitous group of fungal species readily isolated from agroecosystem and natural ecosystem soils which includes important plant and human pathogens. Genetic relatedness within the complex has been studied by sequencing either the genes or the barcoding gene regions within those genes. Phylogenetic analyses have demonstrated a great deal of diversity which is reflected in the differing number of clades identified: three, five and eight. Genetic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 75 publications
1
39
0
Order By: Relevance
“…Following the most common species concept used in fungi, the Phylogenetic Species Concept (PSC) [ 6 ], a species is assigned to a phylogenetic cluster that shares a most recent common ancestor, and it differs phenotypically from its closest relatives [ 8 , 10 ]. However, this is not always observed in the genus Diaporthe , as in the case of the Diaporthe eres complex, which was shown in this study to display little or no morphological variation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the most common species concept used in fungi, the Phylogenetic Species Concept (PSC) [ 6 ], a species is assigned to a phylogenetic cluster that shares a most recent common ancestor, and it differs phenotypically from its closest relatives [ 8 , 10 ]. However, this is not always observed in the genus Diaporthe , as in the case of the Diaporthe eres complex, which was shown in this study to display little or no morphological variation.…”
Section: Discussionmentioning
confidence: 99%
“…The Genealogical Concordance Phylogenetic Species Recognition (GCPSR), introduced by Taylor et al [ 6 ], relies in the comparison of individual gene genealogies to identify incongruences, and it has been particularly useful to delimit the species boundaries in morphologically conserved fungi [ 7 ]. However, the common approach of concatenating sequence data to delimit species without following the GCPSR principle [ 6 , 8 ] overestimates the true diversity of species, since each clade in combined trees is frequently recognized as a distinct lineage [ 9 , 10 ]. Moreover, species boundaries in closely related taxa can be somehow difficult to determine through multilocus sequence data, as some alleles are not expected to be reciprocally monophyletic in the initial stages of speciation, resulting in phylogenetic incongruences [ 7 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, associating VCGs to host specificity and virulence may be extrapolative, as multiple VCGs can be present in one pathogenic race or vice versa (Krnjaja et al, 2013). Using genealogical concordance phylogenetic species recognition, the FOSC has been phylogenetically reassessed rigorously and recently epitypified (Achari et al, 2020;Laurence et al, 2014;Lombard et al, 2019aLombard et al, , 2019bMaryani et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…pisi race 1 isolate RBG6462, race 2 isolate RBG6423, race 5 isolate RBG6425 and race 6 isolate RBG6418 were single spored as described by Burgess et al [ 99 ] and grown on Potato Dextrose Agar (PDA; Diffco Laboratories, Detroit) under dark incubation for 5 days at 25 °C before using them for preparing inoculum. An earlier study on the phylogenetic relationships of these isolates has placed RBG6462 in clade 3 while the other three isolates were in clade 2 within the FOSC [ 2 ]. Further analysis later predicted RBG6462 as ‘species’ 3 while the other three isolates were assigned as ‘species’ 2 within the FOSC [ 2 ].…”
Section: Methodsmentioning
confidence: 99%
“…pisi (Fop) causes vascular wilt in peas ( Pisum sativum ). Phylogenetic relationship study has shown that isolates of Fop races are polyphyletic and are present in clades 2 and 3 of the Fusarium oxysporum species complex (FOSC) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%